Implications behind the Covid 19: A Profound Structural Change Out Of Catastrophy? - Ferdi T. Güçyetmez; Javaid Ahmad Andrabi; Muhammad Ridwan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
Robert Cox has been the most well-known, and prominent intellectual as well, by articulating the building process of historical bloc within the context of the emergence of social forces initially in the nation-state, and his attempt has culminated in the unquestionable power of transnational power in global political economy for those who has vested interest in the identity of hegemony. By the article, we present a tentative attempt in effect by such a hypothetical assumption that the power configurations of social forces, state and world order fell default in their challenge against the unprecedented Virus pandemic while the virus itself has no such configurations as material capability, idea and institutions. The Covid 19 set up its own hegemony literally. The global politics has always been exposed to independent variables not predicted even though collectively or individually measures are taken by states. In this study, we will talk about the emergence of a new hegemonic power with the Covid 19 Pandemic.